Heatwaves cause relative fitness decline in aquatic insects by altering life history and host–pathogen relationships - Sarah A. Taig; Galen Holt; Georgia K. Dwyer; Rebecca E. Lester (Ecosphere)
Abstract Extreme climatic events are linked to an increase in emergent diseases. Such increases depend on the relationships between environmental conditions and host–parasite dynamics. Caddisflies host the oomycete Saprolegnia, which has increased in prevalence in freshwater systems and causes mortality in caddisflies, most prominently Ulmerochorema rubiconum. We tested how short (12 h) or longer (21 days) heatwaves (22.5°C water temperature) alter U. rubiconum hatching and Saprolegnia infection in eggs compared to no heatwave (i.e., ongoing low temperatures at 12.5°C). Short and longer heatwaves yielded similarly elevated infection probability compared to no heatwaves. A longer heatwave shortened the egg period significantly compared to a short heatwave or no heatwaves. As short heatwaves increased infection probability and resulted in longer egg durations than longer heatwaves, they could pose a greater risk to caddisfly populations than the longer heatwaves. Population modeling demonstrates how this hatching‐infection trade‐off determines the effect of heatwaves on population growth rates. Predicted increases in heatwave frequency and magnitude increased the likelihood that eggs would experience conditions favorable for infection, potentially disrupting caddisfly populations and ecosystem functioning. Similar asymmetric impacts of climate on ecological relationships are likely common and may yield important population outcomes. The responses of hosts and pathogens to change must be studied in unison, rather than individual components in isolation.